No Way to Pick a President - Witcover, Jules (New York Routliedge, 2001)
Witcover reveals how professional mercenaries, driven by an insatiable need for money, are poisoning public life. Meanwhile, politicians encourage this development, responding to the demands of a media-driven age. Sharp and revealing.
Include Bibliography and Index
Keywords: Political campaigns -- Presidents--Election -- United States -- Politics and government